2023
DOI: 10.12982/nlsc.2023.005
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Potential of Red Betel (Piper crocatum) Leaves Through Inhibitory Mechanism on Nfκb Signaling Pathway: Drug-Like Candidate Study

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease that causes inflammation of the synovial tissue bone as well as joint damage. Furthermore, an increase in the level of pro-inflammatory cytokines, such as tumor necrosis factor α (TNF-α) due to overexpression in the nuclear factor-kappa B (NFκB) contributes to the progression of the disease. NFκB also plays an important role in the production, differentiation, and effector function of inflammatory T cells. Red betel (Piper crocatum) leaf (RBL) is an In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This result suggested that the anti-osteoclastic effect of hydroxychavicol is mediated at least in part by the inhibition of NF-κB pathway. A molecular docking study suggested that hydroxychavicol has an affinity to bind to the inside of the IKK binding pocket ( Maslikah et al ., 2023 ). This suggests that IKK may be a target of hydroxychavicol; however, the possibility of interrupting the binding of RANKL to receptor by hydroxychavicol cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that the anti-osteoclastic effect of hydroxychavicol is mediated at least in part by the inhibition of NF-κB pathway. A molecular docking study suggested that hydroxychavicol has an affinity to bind to the inside of the IKK binding pocket ( Maslikah et al ., 2023 ). This suggests that IKK may be a target of hydroxychavicol; however, the possibility of interrupting the binding of RANKL to receptor by hydroxychavicol cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%